2020
DOI: 10.1002/anie.201915615
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of [2Fe–2S]‐Cluster‐Bridged Protein Complexes and Reaction Intermediates by use of Native Mass Spectrometric Methods

Abstract: Many iron–sulfur proteins involved in cluster trafficking form [2Fe–2S]‐cluster‐bridged complexes that are often challenging to characterize because of the inherent instability of the cluster at the interface. Herein, we illustrate the use of fast, online buffer exchange coupled to a native mass spectrometry (OBE nMS) method to characterize [2Fe–2S]‐cluster‐bridged proteins and their transient cluster‐transfer intermediates. The use of this mechanistic and protein‐characterization tool is demonstrated with hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…BOLA3 is known to form a hetero-dimeric complex with apo GLRX5 with an affinity constant of 1.2 × 10 5 M −1 [22][23][24][25]. To test whether the Cys59Tyr mutation affected the formation of the apo BOLA3-GLRX5 complex, we stepwise added apo GLRX5 to 15 Nlabelled C59Y BOLA3, or vice versa adding C59Y BOLA3 to apo 15 N-labelled GLRX5, and the interaction was followed through 1 H− 15 N HSQC NMR experiments (see the Materials and Methods section for details).…”
Section: Cys59tyr Bola3 Mutation Modified the Interaction Of Bola3 With Apo Glrx5mentioning
confidence: 99%
See 2 more Smart Citations
“…BOLA3 is known to form a hetero-dimeric complex with apo GLRX5 with an affinity constant of 1.2 × 10 5 M −1 [22][23][24][25]. To test whether the Cys59Tyr mutation affected the formation of the apo BOLA3-GLRX5 complex, we stepwise added apo GLRX5 to 15 Nlabelled C59Y BOLA3, or vice versa adding C59Y BOLA3 to apo 15 N-labelled GLRX5, and the interaction was followed through 1 H− 15 N HSQC NMR experiments (see the Materials and Methods section for details).…”
Section: Cys59tyr Bola3 Mutation Modified the Interaction Of Bola3 With Apo Glrx5mentioning
confidence: 99%
“…BOLA3 is known to form a hetero-dimeric complex with apo GL constant of 1.2 × 10 5 M −1 [22][23][24][25]. To test whether the Cys59Tyr muta mation of the apo BOLA3-GLRX5 complex, we stepwise added apo G C59Y BOLA3, or vice versa adding C59Y BOLA3 to apo 15 N-labelled teraction was followed through 1 H− 15 N HSQC NMR experiments (s As following step, chemical shift perturbations and line broadening analyses were performed by comparing the 1 H− 15 N HSQC spectra of 15 N-labelled BOLA3 and 15 Nlabelled C59Y BOLA3, respectively, with those recorded in presence of equimolar amounts of apo GLRX5, at two different starting concentrations of 15 N-labelled BOLA3 and 15 Nlabelled C59Y BOLA3 (100 and 800 µM).…”
Section: Cys59tyr Bola3 Mutation Modified the Interaction Of Bola3 Withmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that [2Fe-2S]bound BOLA3-GLRX5 heterodimeric complex is indeed well-suited for cluster trafficking, with cluster uptake from donors such as ISCU or [2Fe-2S](GS) 4 resulting in the [2Fe-2S]-bridged BOLA3-GLRX5 complex, and the [2Fe-2S] in BOLA3-GLRX5 readily transferrable to downstream cluster acceptors [9,16], but not to ISCA1 or ISCA2 that has been implicated in [4Fe-4S] cluster trafficking [9].…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41] Recently, native MS has been applied to a much broader range of Fe-S proteins, enabling the determination of cluster types, and, remarkably, the nature of chemistry taking place at clusters, in some cases in real time. [42][43][44][45][46][47][48][49][50][51][52] Aspects of these advances are the focus of this article.…”
mentioning
confidence: 99%